An overview of polyoxymethylene dimethyl ethers as alternative fuel for compression ignition engines. (15th June 2022) - Liu, Junheng; Wang, Lejian; Wang, Pan; Sun, Ping; Liu, Haifeng; Meng, Zhongwei; Zhang, Lidong; Ma, Hongjie
Highlights: The synthetic technology of PODE and the prospect for alternative fuels are assessed. The physicochemical and spray characteristics of PODE blended fuels are detailed. The application of PODE increases thermal efficiency and reduces certain emissions. The benefits of using PODE for advanced combustion modes are discussed in detail. The latest research progress on the oxidation mechanisms of PODE is summarized. Abstract: The application of oxygenated alternative fuels in diesel engines is an effective solution to the energy crisis and environment pollution. Polyoxymethylene dimethyl ethers (PODE), as a coal-based and biomass oxygenated fuel, is considered to be a new promising alternative fuel for petroleum due to its good physicochemical properties and excellent combustion and emission characteristics in engines. The application advantages of PODE are mainly reflected in reducing particulate matter and greenhouse gases, achieving carbon neutrality and fuel diversification, alleviating energy shortages, solving methanol overcapacity and so on. In the review, the manufacturing processes, synthetic methods and raw materials of PODE are expounded in order to comprehend the production capacity and economic value. Then, the physicochemical properties and the spray and atomization characteristics of PODE and PODE blended fuels are summarized, and the advantages and disadvantages of PODE engine are discussed in detail. The applications of PODE in engines are classified and summarized from two aspects: (1) PODE as an additive to improve fuel properties of diesel engines, (2) PODE applied in advanced combustion modes, including homogeneous charge compression ignition, premixed charge compression ignition and reactivity controlled compression ignition. Related studies demonstrate that PODE is a better choice to replace gasoline or diesel fuel in terms of engine performance, combustion and emission characteristics. Finally, the oxidation mechanisms of PODE are summarized, and the future research directions of PODE are also proposed. A comprehensive review of the published literature will help researchers understand the latest technologies and forward theories of PODE applied in the engine.